EFEKTIVITAS MODEL PEMBELAJARAN QUANTUM LEARNING TERHADAP HASIL BELAJAR IPAS SISWA KELAS 3 SEKOLAH DASAR - Nurlaila; Rayi Siti Fitriani; Apriliani Nurcahya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This This study aimed to examine the effect of the Quantum Learning model based on the TANDUR strategy on the Science and Social Studies (IPAS) learning outcomes of third-grade students at SD IT Jaya Bakti on the topic of the animal life cycle. The study employed a Pre-Experimental method using a One-Group Pretest–Posttest design. Data were collected through pre-tests, post-tests, observation sheets, and questionnaires. The descriptive analysis indicated an increase in the students' mean learning outcomes, from 40.00 on the pre-test to 48.33 on the post-test. However, the results of the Paired Samples t-Test revealed a significance value (Sig. (2-tailed)) of 0.224 (p > 0.05), indicating that the improvement was not statistically significant. Furthermore, the N-Gain analysis produced an average score of 0.0086 (0.86%), which falls into the low category. The absence of a statistically significant effect may have been influenced by the relatively small sample size, which limited the statistical power of the analysis. In addition, during the implementation of the learning activities, two students experienced difficulties maintaining concentration, resulting in lower post-test scores that affected the overall class average. Nevertheless, the findings from the observations and questionnaires suggest that the implementation of the Quantum Learning model based on the TANDUR strategy was effective in creating a more active, interactive, and enjoyable learning environment, while also enhancing students' self-confidence during the learning process. Therefore, this instructional model demonstrates practical potential for improving IPAS learning, particularly when implemented with a larger sample size, a longer intervention period, and more conducive classroom conditions.